Do Concurrent Peri-Implantitis and Periodontitis Share Their Microbiotas? A Pilot Study - Ana Parga; José Manuel Pose-Rodríguez; Andrea Muras; María Baus-Domínguez; Paz Otero-Casal; Marcos Luis Ortega-Quintana; Daniel Torres-Lagares; Ana Otero (MDPI AG, 2024)
The microbial compositions from concurrent peri-implant and periodontal lesions were compared, since the results reported in the literature on the etiological relationship between these oral pathologies are contradictory. Microbial compositions from nine patients were evaluated using Illumina MiSeq sequencing of 16S rRNA gene amplicons and Principal Components Analysis. Comparisons between the use of curettes or paper points as collection methods and between bacterial composition in both pathologies were performed. Paper points allowed the recovery of a higher number of bacterial genera. A higher bacterial diversity was found in peri-implantitis compared to periodontal samples from the same patient, while a greater number of operational taxonomic units (OTUs) were present in the corresponding periodontal samples. A higher abundance of oral pathogens, such as Porphyromonas or Treponema, was found in peri-implantitis sites. The opposite trend was observed for Aggregatibacter abundance, which was higher in periodontal than in peri-implantitis lesions, suggesting that both oral pathologies could be considered different but related diseases. Although the analysis of a higher number of samples would be needed, the differences regarding the microbial composition provide a basis for further understating the pathogenesis of peri-implant infections.